The restless universe : applications of gravitational n-body dynamics to planetary, stellar and galactic systems : proceedings of the fifty-fourth Scottish Universities Summer School in Physics, Blair Atholl, 23 July - 5 August 2000 /: applications of gravitational n-body dynamics to planetary, stellar and galactic systems : proceedings of the fifty-fourth Scottish Universities Summer School in Physics, Blair Atholl, 23 July - 5 August 2000. (2019) - Unknown
No abstract available